2016
DOI: 10.1039/c6ra02973f
|View full text |Cite
|
Sign up to set email alerts
|

Citrate complexation microwave-assisted synthesis of Ce0.8Zr0.2O2nanocatalyst over Al2O3used in CO oxidation for hydrogen purification: influence of composite loading and synthesis method

Abstract: Nanostructured Ce0.8Zr0.2O2/Al2O3 composite catalyst was synthesized by modified citrate complexation method. Utilizing microwave combustion endowed the sample with more uniform and homogenous pattern leading to better CO oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Fair number of attempts have also been made to prepare supported simple metal oxide (CoO x , Co 3 O 4 , NiO, Fe 3 O 4 , SnO 2 , CeO 2 , TiO 2 ) nanocatalysts for application in petrochemical industry. 75,[160][161][162][163][164][165][166] In order to improve the catalytic activity as well as versatility in application potential of simple metal or metal oxide nanocatalysts, investigations on supported bimetal, [171][172][173][174][175][177][178][179][180][181][182][183][184][185][186][187] mixed metal oxide [188][189][190][191][192][193]196,197 and ternary metal 198,199 nanocatalysts are also available. MW assisted synthesis has been claimed to be economically viable short green method to produce supported nanocatalyst.…”
Section: Catalysis By Supported Simple Metal Catalystsmentioning
confidence: 99%
“…Fair number of attempts have also been made to prepare supported simple metal oxide (CoO x , Co 3 O 4 , NiO, Fe 3 O 4 , SnO 2 , CeO 2 , TiO 2 ) nanocatalysts for application in petrochemical industry. 75,[160][161][162][163][164][165][166] In order to improve the catalytic activity as well as versatility in application potential of simple metal or metal oxide nanocatalysts, investigations on supported bimetal, [171][172][173][174][175][177][178][179][180][181][182][183][184][185][186][187] mixed metal oxide [188][189][190][191][192][193]196,197 and ternary metal 198,199 nanocatalysts are also available. MW assisted synthesis has been claimed to be economically viable short green method to produce supported nanocatalyst.…”
Section: Catalysis By Supported Simple Metal Catalystsmentioning
confidence: 99%
“…Microwave irradiation as a novel technology has been widely considered in chemical reactions (Ajamein and Haghighi, 2016;Rezaee and Haghighi, 2016) and it has been extensively studied in the field of biodiesel production in order to reduce production and separation times. Refaat et al reported that, in addition to the reduction of the transesterification reaction time (from 75 to 4 min), the separation time was also reduced (from 60 to 3 min) (Refaat and El Sheltawy, 2008).…”
Section: Introductionmentioning
confidence: 99%